A Novel Electrochemical Sensor Based on Samarium Vanadate and Single-Walled Carbon Nanotubes for the Determination of Paracetamol. Issue 8 (1st August 2022) - You, Ya; Zou, Jiao; Jiang, Xin-Yu; Yu, Jin-Gang
Abstract : In this work, samarium vanadate (SmV) and single-walled carbon nanotubes (SWCNTs) were self-assembled by ultrasonic treatment to obtain a novel SmV/SWCNTs nanocomposite. Subsequently, an electrochemical sensor based on SmV/SWCNTs nanocomposite modified glassy carbon electrode (GCE) was constructed. SmV/SWCNTs/GCE exhibited high selectivity, excellent anti-interference, good stability and reproducibility toward paracetamol (PA) detection. The outstanding performances of the developed electrochemical sensor could be mainly attributed to its high electrocatalytic activity for PA, which might be caused by the synergistic effect of SmV and SWCNTs. Under optimized experimental conditions, SmV/SWCNTs/GCE exhibited a good linear relationship between current signal and PA concentration over a wide concentration range 1–100 μ M, and limit of detection (LOD) (signal-to-noise ratio of 3, S/N = 3) was calculated to be 0.035 μ M. The satisfactory recoveries of 98.06%–104.20% and 98.55%–101.88% could be obtained in the bovine serum and PA tablet samples, respectively. We anticipated this work could provide a reference for the future development and application of samarium-based materials in the field of electroanalysis.